State-dependent fractional plasticity model for the true triaxial behaviour of granular soil - Sun, Y.; Sumelka, W. (Archives of Mechanics, 2019)
The fractional plasticity was proposed to model the stress-strain behaviour of granular soils, but only within the scope of classical triaxial loading condition. In this study an attempt is made to develop a 3D fractional plasticity model for granular soils subjected to true triaxial loads by using characteristic stress, where all the fractional-order and integer-order derivatives can be easily obtained. Without using a plastic potential, the non-associated plastic flow rule is achieved by performing fractional derivatives of the yielding function in the characteristic stress space. The obtained plastic flow direction is found to be influenced by the fractional order, characteristic stress parameter and intermediate stress ratio. To further validate the proposed model, a series of true triaxial test results of different granular soils are simulated, from which good agreement between the model predictions and the corresponding test results is found.